COX-2 promotes mammary adipose tissue inflammation, local estrogen biosynthesis, and carcinogenesis in high-sugar/fat diet treated mice. (1st April 2021) - Gonçalves, Rosângela Mayer; Delgobo, Marina; Agnes, Jonathan Paulo; das Neves, Raquel Nascimento; Falchetti, Marcelo; Casagrande, Tuany; Garcia, Ana Paula Vargas; Vieira, Thaynan Cunha; Somensi, Nauana; Bruxel, Maciel Alencar; Mendes, Daniel Augusto Gasparin Bueno; Rafacho, Alex; et al.
Abstract: Obesity is a major risk factor for breast cancer, especially in post-menopausal women. In the breast tissue of obese women, cyclooxygenase-2 (COX-2)-dependent prostaglandin E2 (PGE2) production has been correlated with inflammation and local estrogen biosynthesis via aromatase. Using a mouse model of 7, 12-dimethylbenz[ a ]anthracene/medroxyprogesterone-acetate (DMBA/MPA)-induced carcinogenesis, we demonstrated that an obesogenic diet promotes mammary tissue inflammation and local estrogen production, and accelerates mammary tumor formation in a COX-2-dependent manner. High-sugar/fat (HSF) diet augmented the levels of the pro-inflammatory mediators MCP-1, IL-6, COX-2, and PGE2 in mammary tissue, and this was accompanied by crown-like structures of breast (CLS-B) formation and aromatase/estrogen upregulation. Treatment with a COX-2 selective inhibitor, etoricoxib, decreased PGE2, IL-6, MCP-1, and CLS-B formation as well as reduced aromatase protein and estrogen levels in the mammary tissue of mice fed a HSF diet. Etoricoxib-treated mice showed increased latency and decreased incidence of mammary tumors, which resulted in prolonged animal survival when compared to HSF diet alone. Inhibition of tumor angiogenesis also seemed to account for the prolonged survival of COX-2 inhibitor-treated animals. In conclusion, obesogenic diet-induced COX-2 is sufficient to trigger inflammation, local estrogen biosynthesis, and mammary tumorigenesis. Highlights: HSF diet accelerates mammary tumor formation in mice exposed to carcinogen. COX-2 inhibitor etoricoxib attenuates HSF diet-induced mammary carcinogenesis. Etoricoxib prevents diet-induced CLS-B structures formation in the mammary tissue. Etoricoxib decreases mammary tissue levels of PGE2, IL6 and MCP-1 in mice fed HSF diet. Diet-induced COX-2 promotes aromatase and estrogen synthesis in the mammary tissue.